2014
DOI: 10.1007/s12522-014-0192-2
|View full text |Cite
|
Sign up to set email alerts
|

Acceptable pregnancy rate of unstimulated intrauterine insemination: a retrospective analysis of 17,830 cycles

Abstract: PurposeTo evaluate the pregnancy rate (PR) of unstimulated intrauterine insemination (IUI).MethodsThis was a retrospective study in a private fertility clinic. Between 2004 and 2013, a total of 4,045 women underwent 17,830 cycles of unstimulated IUI. The etiologies of subfertility in the couples were unexplained (51 %), male factor (36 %), coital problems (9.5 %), and cervical factor (3.5 %).ResultsThe PRs/cycle, between the 1st and 9th trials, in women <35, 35–37, 38–40, 41–42, and >42 years of age were 8.2, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 10 publications
2
16
2
Order By: Relevance
“…Intrauterine insemination (IUI) has been widely used for the treatment of infertile couples with mild male factor or unexplained infertility, or with hyposecretion of cervical mucus after conization of the cervix . Compared with assisted reproductive technology (ART), IUI provides a more natural fertilization environment, is less invasive and expensive, and is easier to perform .…”
Section: Introductionmentioning
confidence: 99%
“…Intrauterine insemination (IUI) has been widely used for the treatment of infertile couples with mild male factor or unexplained infertility, or with hyposecretion of cervical mucus after conization of the cervix . Compared with assisted reproductive technology (ART), IUI provides a more natural fertilization environment, is less invasive and expensive, and is easier to perform .…”
Section: Introductionmentioning
confidence: 99%
“…It remains controversial whether ovarian stimulation improved the outcome of IUI treatment in ovulatory women. Some investigators have suggested a beneficial effect, whereas others observed no benefit . In some cases, the protocols of ovarian stimulation were clearly defined, but in others, different protocols were grouped together .…”
Section: Discussionmentioning
confidence: 99%
“…Some investigators have suggested a beneficial effect, 12,14 whereas others observed no benefit. 11 In some cases, the protocols of ovarian stimulation were clearly defined, 12,15 but in others, different protocols were grouped together. 13,14 In our study when all ovarian stimulation protocols were lumped together, we could not find any difference in pregnancy or live birth rate.…”
Section: Discussionmentioning
confidence: 99%
“…Our results are in accordance with three RCTs summarized by Cohlen et al [33], where no significant differences in clinical pregnancy or live birth rate were found between various time frames of that ranged. [20] discovered that the trend of pregnancy rates relevant to cycle number was different according to female age: significantly higher in the first three cycles than in the 4th to 6th cycles or 7th to 9th cycles when women less than 40 years old but no difference was observed at the age over 41 years old. In contrast to the results above, in our study CPR remained stable from the first to the sixth cycle, which was supported by Merviel et al [3].…”
Section: Timing Of Inseminationmentioning
confidence: 99%